REPRESENTASI FEMINISME DALAM KARYA SASTRA (Kajian Semiotika Novel “Eks Parasit Lajang” Karya Ayu Utami) - Sandra Olifia (SEMIOTIKA: Jurnal Komunikasi, 2016)
Literature as one means disclosure of a person's thoughts expressed in text form either used as an expression that is packaged in a special language involving the use of symbols and signs. Inside the novel "Confessions of Ex Parasite Single" by Ayu Utami, clad in deep social and feminine side of writing using signs and symbols function as the author attempts to lift the value of gender from a different angle. The purpose of this study is to determine how the meaning of “Confession Ex Parasite Single” novel by the use of signs and symbols along with the relation both through semiotic approach from Elaine Showalter. Based on the results of this study can be explained that the author seeks to elevate feminism in terms of resistance to the values of cultural and religious norms, especially in addressing the virginity resulting in suppression of meaning radically in providing a perspective on the value of these gender perceive the culture of patriarchy begin a history of oppression of women with negative stigmatization against woman's bodies.Keywords: Text and Culture, Representation, Feminism